2011
DOI: 10.1029/2010gl046152
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to estimate DOC concentrations from CDOM absorption coefficients in coastal waters

Abstract: [1] A novel method to accurately retrieve DOC concentrations (±4%) from CDOM absorption coefficients, a g (l), at l = 275 and 295 nm is presented. By using these two wavelengths, the method exploits useful information about the ratio of a g (l) to [DOC] contained in the 275-295 nm spectral slope coefficient, S 275−295 . This approach was developed using data (n = 222) collected on a seasonal basis in surface waters of the Northern Gulf of Mexico. The approach is demonstrated to accurately and consistently est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(221 citation statements)
references
References 18 publications
13
206
2
Order By: Relevance
“…In this study, we found that DOC concentrations were highly correlated with a CDOM (440) in the UPML (r 2 = 0.97), which is consistent with recent papers (e.g., Mannino et al, 2008;Fichot and Benner, 2011). In particular, our regression was similar with that obtained in the U.S. Middle Atlantic Bight (Mannino et al, 2008;DOC vs. a CDOM (440) relationship was obtained assuming a S CDOM of 0.018 nm −1 to convert a CDOM (412) to a CDOM (440)).…”
Section: Implications For Estimating Doc Concentrations Insupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that DOC concentrations were highly correlated with a CDOM (440) in the UPML (r 2 = 0.97), which is consistent with recent papers (e.g., Mannino et al, 2008;Fichot and Benner, 2011). In particular, our regression was similar with that obtained in the U.S. Middle Atlantic Bight (Mannino et al, 2008;DOC vs. a CDOM (440) relationship was obtained assuming a S CDOM of 0.018 nm −1 to convert a CDOM (412) to a CDOM (440)).…”
Section: Implications For Estimating Doc Concentrations Insupporting
confidence: 92%
“…In contrast, there is a significant and positive correlation between this absorption and chlorophyll-a (chl-a) concentration in oceanic waters, suggesting phytoplankton-derived components contribute to CDOM (e.g., Bricaud et al, 2010). In addition, the spectral slope of CDOM absorption can give insights about sources and the bulk chemical properties of CDOM (Carder et al, 1989;Helms et al, 2008;Fichot and Benner, 2011), which are possibly influenced by photochemical and/or biological processes (e.g., Twardowski and Donaghay., 2002;Bricaud et al, 2010). Thus, CDOM absorption properties provide insights about source and physicochemical and biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral slopes are lower compared to mean Baltic and North Sea detritus absorption slopes, which are 0.013 and 0.0116 nm −1 , respectively (Babin et al, 2003a). Ferrari et al (2003) reported values between 0.0095 and 0.0125 nm −1 for the Baltic Sea. These are similar to values found in the NOMAD database (Werdell and Bailey, 2005) which are in the range 0.007-0.015 m −1 (5-95 % percentile).…”
Section: Discussionmentioning
confidence: 80%
“…Chromophoric DOM (CDOM), the colored component of DOM primarily absorbs light in the UV and visible spectral range affecting the intensity and spectral quality of the light field in the aquatic medium. Because in situ measurement and analysis of DOC is time-consuming and expensive [4,5], the potential for satellite estimates of DOC could provide a useful tool with synoptic and repeated coverage. However, DOC cannot be sensed directly by ocean color sensors; CDOM, the colored fraction of DOC, can be estimated remotely.…”
Section: Introductionmentioning
confidence: 99%